ORGANISATIONAL CULTURE AND EMPLOYEE PERFORMANCE IN DEPOSIT MONEY BANKS IN YENAGOA, BAYELSA STATE, NIGERIA (American Journal of Research in Humanities and Social Sciences, 2025)
The study investigated organisational culture and employees’ performance of deposit money banks in Yenagoa, Bayelsa State, Nigeria using four objectives. This study employs a descriptive survey research design and utilizes a quantitative research method by distributing an online questionnaire through the use of Google Form.